Model Konseptual Sistem Informasi sebagai Penunjang Operasional Perusahaan Dagang - Oktavia, Tanty (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Many ways are taken to be superior in the existing competition, such as differentiation products, identifing new marketing strategies, and improving the performance of operational activities in order to obtain positive responses from the customer. The role of the customer in the implementation of a trading company holds an important position because of all the activities carried out focus on how companies can build satisfaction for the customer, so that in the future they will be back to the company'. This research discusses the design of an information systems to support the implementation of the company's daily operation which consists of selling activities, purchasing, and stock. The method used consists of analysis and design. Analysis begins from the identification of operational processes and data used in daily trading company in general, equipped with some concepts from supporting research literature to develop a model that can be applied. Meanhile the design method through the object oriented approach are illustrated using diagrams Unified Modelling Language (UML). A conceptual model of information system that can be implemented in support of the company's trading operations, which can provide competitive advantage for the company to face competition in the industry.